Retropharyngeal abscess: seven-year review - clinical presentation, diagnosis and management - Abdul Fattah AW,; Marina MB,; Mazita A,; Muhammad Razif MY,; Primuharsa Putra SHA, (Penerbit UKM, 2009)
This was a retrospective study of operative records between 2000 – 2007 from two ear, nose and throat (ENT) referral centers in Malaysia to review demographic patterns, clinical presentations and management of retropharyngeal abscess (RPA). Our case series comprised of eight patients with five females and three males with a median age at presentation of 47 years. Comorbid factor in this series was diabetes mellitus, with four patients having diabetes. There were three cases of fish bone ingestion. The commonest presentation was dysphagia or odynophagia. None of them had fever. All patients were treated with broad spectrum intravenous antibiotics (IV) and drainage was performed for the abscess. Four patients underwent transoral drainage with three having the cervical approach and one having spontaneous rupture.All patients recovered well from the infection and only one patient passed away due to septicaemia. In conclusion, patients with retropharyngeal abscess may present with vague symptoms of sore throat, odynophagia without fever due to partial antibiotics treatment. A correct diagnosis should be made so that adequate treatment can be given to prevent mortality.